Tissue and cell imaging in situ: potential for applications in pathology and endoscopy. (1st June 2003) - Scoazec, J-Y
Abstract : Morphological sciences have recently experienced a significant technological breakthrough that offers new opportunities for cell and tissue imaging in situ but also raises new challenges to pathologists, who must adapt to a rapidly evolving environment. New partners, such as cell and molecular biologists, have provided pathologists with highly powerful tools for cell and subcellular imaging. They include: (a) the adaptation of techniques derived from molecular biology and cytogenetics, (b) the development of new microscopic tools, such as confocal microscopy, and (c) the emergence of new preparative techniques, such as microdissection or tissue arrays. However, recent technological progresses in various fields, from endoscopy to genomics, also raise new challenges to pathologists. Pathologists must therefore be prepared to redefine their area of expertise: this will be achieved through a continuous collaboration with all the partners involved in cell and tissue imaging and analysis but also by emphasising the importance of the informations provided by cell and tissue imaging in situ.